Ответы и объяснения

2013-09-04T12:13:18+00:00
Выражение: 6.2*(3-2*x)=20-(12.4*x+1.4)

Ответ: 0=0

Решаем по действиям:
1. 6.2*(3-2*x)=18.6-12.4*x
  6.2*(3-2*x)=6.2*3-6.2*2*x
  1.1. 6.2*3~~18.6
      X6.2
       _ _3_ _
      18.6
  1.2. 6.2*2=12.4
      X6.2
       _ _2_ _
      12.4
2. 18.6-20=-1.4
  -20.0
   _1_8_._6_
  -01.4
3. -12.4*x+12.4*x=0
4. -1.4+1.4=0
  -1.4
   _1_._4_
   0.0

Решаем по шагам:
1. 18.6-12.4*x-20+12.4*x+1.4=0
  1.1. 6.2*(3-2*x)=18.6-12.4*x
      6.2*(3-2*x)=6.2*3-6.2*2*x
    1.1.1. 6.2*3~~18.6
          X6.2
           _ _3_ _
          18.6
    1.1.2. 6.2*2=12.4
          X6.2
           _ _2_ _
          12.4
2. -1.4-12.4*x+12.4*x+1.4=0
  2.1. 18.6-20=-1.4
      -20.0
       _1_8_._6_
      -01.4
3. -1.4+1.4=0
  3.1. -12.4*x+12.4*x=0
4. 0=0
  4.1. -1.4+1.4=0
      -1.4
       _1_._4_
       0.0